#Metoovertising: the institutional work of creative women who are looking to change the rules of the advertising game. Issue 1 (2nd January 2021) - Thompson-Whiteside, Helen; Turnbull, Sarah
ABSTRACT: In the wake of #MeToo, the ad industry is coming to terms with its own issues of sexual harassment. We therefore explore the institutional work of actors who are constrained by these gendered institutional arrangements and consider how they might be involved in changing the sexist attitudes and behaviours prevalent in ad agencies. We consider the work of Les Lionnes, a collective of women working in French advertising agencies, who form a boundary organisation to address sexual harassment in the French advertising industry. By conducting critical discourse of their 2019 poster campaign, together with a netnographic study of their social media sites and an interview with its founder, we identify how advertising is used to expose the sexist attitudes and behaviours embedded in discourse and challenge the continued legitimacy of institutional logics. The success of this work may be further enhanced when it is aligned with a wider social discourse, such as #MeToo. We therefore conceptualise the advertising undertaken by Les Lionnes as institutional work which seeks to expose sexual harassment and abuse within the ad industry. We call this novel form of advertising #Metoovertising.